PSYCHOSOCIAL ATTACHMENT AS A DRIVER OF ALUMNI ENGAGEMENT IN TVET INSTITUTIONS IN MALAYSIA - Hadijah Kodiron; Shameira Apandi; Zuraini Zainal Abidin (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
This study examines the role of alumni psychosocial attachment as a key driver of alumni engagement in Technical and Vocational Education and Training (TVET) institutions in Malaysia, while also evaluating the mediating role of institutional support. Many higher education institutions, including TVET colleges, seek to foster lasting relationships with their graduates to build support networks and enhance institutional reputation, but often struggle to understand the key drivers that lead to sustained alumni engagement. The research introduces a focused investigation into psychosocial attachment—comprising dimensions of connectedness and gratitude—as a primary driver of alumni engagement within the TVET context, and uniquely tests institutional support as a mediating variable in this relationship. A quantitative survey-based design was employed, involving 410 alumni from TVET institutions under the Department of Polytechnic and Community College Education (JPPKK). Data were analysed using descriptive statistics, Pearson correlation, and hierarchical multiple regression. The level of alumni psychosocial attachment (connectedness and gratitude) is high. A strong and statistically significant positive relationship exists between psychosocial attachment and alumni engagement. Hierarchical regression analysis shows that institutional support does not function as a mediating variable, as its contribution is minimal and statistically insignificant. Psychosocial attachment is a critical direct determinant of alumni engagement, while institutional support does not play a mediating role. The findings emphasize the need for TVET institutions to strengthen psychosocial bonds with students early in their educational journey to foster lasting post-graduation engagement.